Kedudukan Izin Lingkungan Dalam Sistem Perizinan Di Indonesia - Helmi ' (Fakultas Hukum Universitas Riau, 2011)
As an instrument of environmental resource management, environmental permits has an important position. Lay No. 32 of 2009 on the Protection and Environmental Management (UU-PPLH) permits the integration of various environmental permits before splitting. But the problems faced, it turns out, the law it self is still not firmly UU-PPLH provide the scope and type environmental permit it self. Status of environmental permits for a business license or activities appear on the scope and legal relations of both, which is an instrument of obtaining environmental permits and business licenses or implement environmental management activities.